Fatores associados ao absenteísmo doença entre motoristas e cobradores de ônibus da Região Metropolitana de Belo Horizonte: doença entre motoristas e cobradores de ônibus da Região Metropolitana de Belo Horizonte - Sebastião Sérgio de Oliveira Rodrigues (2015)
Sickness absenteeism has become a very important issue for public health in Brazil and abroad. This is due to the negative consequences on the state of well-being of workers and on the management of public or private organizations. Workers in urban transportation have a greater risk of illness when compared to professionals in other categories, due to physical and mental stress they undergo. This research, noting such facts presented, aimed to investigate how the working conditions of the RMBH (Região Metropolitana de Belo Horizonte) urban transportation workers influence the phenomenon of sickness absenteeism, evaluating the prevalence and factors involved in its occurrence. Through cross-sectional study, a sample of 1,607 workers of the urban public transport, coming from the cities of Belo Horizonte, Contagem and Betim (MG), was investigated. These workers underwent face to face interviews using a questionnaire with sociodemographic, lifestyle, occupational, health and violence/victimization approach. The dependent variable, sickness absenteeism, was based on the answer to the question: "In the last 12 months, you missed work due to health problems?", with response options: Yes / No. The data obtained by the questionnaire, concerning the selected variables were submitted to univariate analysis using Poisson regression with robust variance. Those that were associated to the level of 20% significance (p0,20) were selected for multiple analysis within each of the blocks of independent variables. The independent variables were entered into an analysis model with hierarchical entry in affinity blocks, following this order: sociodemographic and lifestyle (level 1 - distal); occupational factors (level 2 - intermediate) and health-related factors (level 3 - proximal). Remained the explanatory variables with p0.05, which were inserted starting with the most statistically significant variable and following, the other variables were added one by one in descending order of the descriptive level. In the final model multivariate remained all the variables that were significantly associated with the outcome at 5% (p 0.05 value). The magnitude of association between dependente variable and independent variables was estimated by the prevalence ratio (PR) with their respective confidence intervals. The prevalence of absenteeism and illness in the last 12 months was 37,4%. There was a statistically significant association between sickness absenteeism the following variables: victim of aggression or threat: occasionally / frequently (PR = 1,32; CI95%:1,07-1,62); feel the body vibration in the workplace: occasionally / rarely (PR = 1,33; CI95%:1,01-1,74), always or almost always (PR = 1.41; CI95%: 1.09-1.82); positive test for CMD (PR = 1.33; CI95%: 1.07-1.65) and diagnosed diseases: one or two diseases (PR = 1.54; CI95%: 1.16-2,03), three or more diseases (PR = 1.94; CI95%: 1.46-5.57). The results of the study showed that the working conditions of the urban bus drivers and conductors from the RMBH constitute themselves as a priority for intervention actions aimed at improving the prevention of diseases and subsequent sickness absenteeism, besides reducing burdens on companies and previdenciary system. Thus, future researches are suggest to investigate in more detail the working conditions and the factors involved in sickness process of urban bus drivers and conductors from RMBH.